Chemistry of the unusually high uptake and recovery of gas-phase Hg0 by TiO2 even under household fluorescent lights - Jung Hoon Lim (Elsevier, 2021)
Reaction mechanisms for the removal of Hg0 by a TiO2 photocatalyst in the presence of O2, the main electron acceptor for the photocatalyst, were proposed. The Hg0 removal efficiency was over 90%, and the desorption efficiency was approximately 70%. As the photocatalyst reacted with Hg0, TiO2 was activated, forming OH radicals on the surface that oxidized Hg. HgO was formed in the first layer, and Hg0 was captured. Then, oxidized Hg acted as an electron acceptor. Physical adsorption between Hg0 molecules was realized by the reaction of Hg0 and HgOH. The adsorption of Hg0 was analyzed by various surface analysis methods, and the results proved that physical and chemical adsorption occurred. After this adsorption, desorption with alcohol was performed. Hg0 was desorbed, and HgO was reduced by the simultaneous illumination by light and addition of alcohol. The analytical and calculated values were compared for quantitative confirmation.